Role of intravenous immunoglobulins in the management of systemic lupus erythematosus: a single-centre experience - Sedat Yılmaz; Mehmet Nur Kaya; Özlem Kılıç; Muhammet Canbaş; Merve Sungur Özgünen; Ezgi Çimen Güneş (Lupus Science and Medicine)
Objectives Systemic lupus erythematosus (SLE) is a chronic autoimmune disease of unknown aetiology that can affect almost any organ in the body. Although there are no specific guidelines for the use of intravenous immunoglobulin (IG) in the treatment of patients with SLE, it is thought to be an effective treatment. Our study aimed to evaluate the effectiveness and safety of intravenous IG and to describe the possible profile of patients with SLE who are candidates for intravenous IG treatment.Methods This study was designed to retrospectively analyse patients with SLE treated with 2 g/kg/month of intravenous IG (divided across 5 consecutive days). We collected demographic, clinical, laboratory and treatment data from the patient files. The side effects of the intravenous IG treatment, changes in the immunosuppressive therapy used and changes in the clinical and laboratory parameters after the intravenous IG treatment were evaluated.Results This study included 31 patients with SLE. The main indication for intravenous IG treatment was haematological involvement (20, 64.5%) and thrombocytopenia in particular (8, 25.8%). Intravenous IG was initiated mainly for refractory disease. At the end of the treatment, the acute phase values, proteinuria, complement levels and anti-double-stranded DNA decreased significantly (p<0.001). In most cases, the side effects were mild and usually manifested as myalgia or a fever.Conclusion Despite its high cost, intravenous IG has demonstrated effectiveness in treating refractory SLE, especially when there is haematological involvement. Specific clinical features at baseline may identify the patients who are more likely to respond to this therapy.